One-Pot Synthesis of Fused Pyrroles via a Key Gold Catalysis-Triggered Cascade - Zheng, Zhitong (2014)
A two-step, one-pot synthesis of fused pyrroles is realized by firstly condensing N-alkynylhydroxammonium salt with readily enolizable ketone under mild basic condition and then subjecting the reaction mixture to a gold catalyst, which triggers a cascade reaction featured by a facile initial 3.3-sigmatropic rearrangement of the gold catalysis product, i.e., an N,O-dialkenylhydroxamine. The reaction provides a facile access to polycyclic pyrroles in moderate to good yields.